Pokok-pokok Pegangan imam-imam mazhab dalam membina hukum islam - T. M. Hasbi Ash Shiddieqy (Bulan Bintang, 1973)
tr, jil. 1=c.1-4; jil.1-2=c.1-6/ast jil.1 =c.5/wk, jl.1=c.6/tr, jil.1=c.7; jil.1-2=c.7-8